Formulation by Design Approach for Fizzy Granules Using Statistical Optimization Methodologies - Ashish Baldi, Dr (Asian Journal of Pharmaceutics (AJP), 2016)
Context: Patient compliance is a major problem in the administration of medicines to pediatric patients mainly due to bitter taste or fear of medication. Therefore, novel formulation development based on current industrial practices is need of the hour. Aims: To prepare fizzy granules of amoxicillin trihydrate using formulation by design (FbD) concept to increase the patient compliance in pediatrics. Settings and Design: Critical process parameters were selected using Plackett–Burman design while their concentrations were optimized by application of response surface methodology using 20 confirmatory runs, which indicated very high degree of prognostic ability of statistical optimization. Low and high levels of each factor represented maximal and minimal settings of wide operational ranges. Materials and Methods: Formulations were prepared by non-aqueous wet granulation method. Statistical Analysis Used: Statistical methodologies were used to screen significant variables and responses, which affect the quality of fizzy formulation. Sodium bicarbonate, polyvinyl pyrrolidone, and lactose were selected as critical excipients, based on t-coefficient values as obtained through Plackett–Burman design. Then, 33 central composite design was employed to systematically optimize these variables and desired quality attributes, particle size (PS), and fizzy time. Contour plots were drawn, and optimum concentrations of selected excipients were determined using point optimization feature. Results: Developed polynomial mathematical models were found suitable to define effervescence time and PS of the optimized formulation with 98.46% and 91.24% validity. Conclusion: FbD concept was successfully applied for the development of fizzy granules as per current quality practices prevailing in pharmaceutical industries.